Path-dependent volatility: an application to the South African market - Sookdeo, Shivan (Division of Actuarial Science, 2018)
Industry and academia have thus far focussed on three classes of volatility models, namely, constant volatility, local volatility and stochastic volatility. Pathdependent volatility models are a lesser known class of models which possess the key characteristic of completeness together with the ability to generate a wide range of volatility dynamics with respect to the underlying asset (Guyon, 2014). This dissertation highlights the usefulness and practicality of these models for application in the South African market, while drawing comparisons with other widely used models. The tests cover both pricing and hedging of vanilla European options on the FTSE JSE Top 40. The Black-Scholes, Heston and CEV models are used as comparative benchmarks for each of the other classes of models.